O letramento afro-literário a partir de contos de autoria Negra - SOUZA, Elcilene Cativo de Oliveira de (Universidade Federal do Oeste do Pará, 2024)
This work reflects on the presence of Afro-Brazilian literature to strengthen anti-racist practices inside and outside the classroom and, more specifically, presents a proposal for an educational product aimed at teachers, from three public schools in Amapá. , with the aim of promoting the inclusion of literary reading of short stories by black authors, in Portuguese language classes in the 9th year of Basic Education. The general objective is to investigate the potential for dialogue between Afro-Brazilian literature and education for ethnic-racial relations, in the light of qualitative research, based on official documents, interviews, courses, lives and, especially, the production of Amâncio (2014), Candido (1995), Dalcastagnè (2011), Duarte (2008; 2014), Debus (2017) Giroto e Souza (2010), Cosson (2018; 2020; 2021), Solé (1998) among others. The research problem sought in this study to know: How can short stories written by Afro-Brazilians contribute to the deconstruction of racist practices and concepts inside and outside the classroom? Why are literary literacy practices important for the continuous reading training of teachers and, consequently, students? The methodology adopted for the educational product proposal consisted of an Afro-literary literacy workshop based on the suggestion of basic sequences and the formation of literature circles, based on the short stories: Pai contra Mãe, by Machado de Assis; Luísa's son, by Joel Rufino dos Santos; Alicerce, by Geni Guimarães; The Flying Carpet, by Cristiane Sobral; Wonder Woman, by Bianca Santana; and in the literary production of Amapá natives Esmeraldina dos Santos, with The Dream of a Girl; Of love and faith, by Ângela Nunes; and The Chosen One, by Manoel Bispo. Among the intended results for continued training for teachers, we proposed the Afro-literary Literacy Workshop in practice (Educational Product), hosted on the Google Classroom virtual platform, based on the possibility of building references to combat discrimination and respect to differences, based on the Afro-literary literacy of teachers and, consequently, of students. Thus, enhancing the implementation of Federal Law No. 10,639/2003 and State Law No. 1,196/2008, with effective racial ambience actions in schools.